Satanisme gesien vanuit "n pastorale perspektief - Bevolo-Manders, J. M. (Hervormde teologiese studies, 1998)
Satanism seen from the perspective of pastoral counselling. Based on observations of Satanism and exorcism, the article suggests that pastors are confronted with two world views which are in conflict with one another: the mythological world view of the New Testament and the modern world view. The article explores the consequences of these conflicting worla views for ministers counselling individuals caught up in the practices of satanism.